The use of NFT technology as a marketing tool for promoting brands in the digital economy - Chukurna, O.P.; Zitar, S.V. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The article discusses new opportunities in brand promotion using alternative platforms, namely, thanks to the new NFT blockchain technologies. The possible development of these technologies in the marketing sphere is considered. Companies that have already managed to master these technologies are proposed for consideration.
Keywords: Blockchain; NFT; marketing; metaverse